Geographic personas : self-transformation and performance in the American West - Allmendinger, Blake (University of Nebraska Press, 2021)
"Geographic Personas explores how writers, dancers, actors, imposters, and con artists were influenced by one or more of three transformative factors -population growth, technology, and literary realism-that contributed to their personal reinvention during a great transitional period in the American West"--